Comparison Between Sedative And Analgesic Effects Of Dexmedetomidine Versus Fentanyl For Pediatric Patients Following Cardiac Surgery In Intensive Care Unit (Journal of Pharmaceutical Negative Results, 2022)
The ICU staff should make careful pharmacological choices for sedation following cardiac surgery. The purpose of this research was to assess the effectiveness and safety of dexmedetomidine versus fentanyl for postoperative sedation, hemodynamic and ventilatory parameters in pediatric patients admitted to the ICU following cardiovascular surgery. A total of 60 pediatric patients admitted to the ICU following heart surgery, ranging in age from one day to fifteen years, and requiring mechanical ventilation upon admission, were included in the prospective and comparative research. They were randomly assigned to one of two groups: Group D (n = 30) receiveddexmedetomidine, whereas Group F (n = 30) received fentanyl. In terms of age, weight, height, gender, and type of surgery, there was no statistically significant difference between the two groups. There were no significant variations in ventilatory measures such as respiratory rate, oxygen saturation, or arterial blood gases in either group when compared to baseline or to each other. There were no significant variations in sedation (COMFORT-B) or pain (FLACC) scores between the two groups. There was no statistically significant difference in the use of rescue sedatives between the two groups. There was a statistically significant difference in intubation length between the two groups. In comparison to fentanyl, dexmedetomidine is a safe and similarly effective medication for the sedation of mechanically ventilated pediatric patients admitted to the ICU following cardiac surgery, with good hemodynamic stability and earlier extubation